1998
DOI: 10.1159/000021462
|View full text |Cite
|
Sign up to set email alerts
|

Working-Day Effects on the Spectral Characteristics of Teaching Voice

Abstract: Ten teachers made recordings during one normal working day using a portable DAT recorder and a head-mounted microphone. In addition, the subjects filled in a questionnaire of signs of vocal fatigue. The speech samples were selected from the first and last lesson from three points representing the beginning, middle and end part of the lesson, respectively. To standardize the samples, 30 [a] vowels from stressed syllables were chosen for spectral analysis. The level of the fundamental and second formant regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 13 publications
3
37
0
2
Order By: Relevance
“…It should also be noted subjects were only asked to report data on the days they taught. The high number of vocal problems reported for some subjects on teaching days (as opposed to sick days taken) may reflect a trend found in other studies that vocal complaints are common among teachers who work despite their vocal discomforts (Rantala, Paavola, Körkkö, & Vilkman, 1998;Sapir et al, 1993).…”
Section: International Journal Of Music Education 25(1)mentioning
confidence: 60%
“…It should also be noted subjects were only asked to report data on the days they taught. The high number of vocal problems reported for some subjects on teaching days (as opposed to sick days taken) may reflect a trend found in other studies that vocal complaints are common among teachers who work despite their vocal discomforts (Rantala, Paavola, Körkkö, & Vilkman, 1998;Sapir et al, 1993).…”
Section: International Journal Of Music Education 25(1)mentioning
confidence: 60%
“…In other studies, the voice has been measured during a workday. In these studies [22][23][24][25]65], differences have been found in individuals who report only few symptoms of voice problems. Field measurements with a voice accumulator have been made in the current subject pool.…”
Section: Voicementioning
confidence: 99%
“…Rantala et al 9,10 or Jonsdottir et al. 11 However, in these studies the influence of the room were not included.…”
Section: Bistafa and Bradleymentioning
confidence: 99%